Corruption and cheating: Evidence from rural Thailand - Olaf Hübler; Melanie Koch; Lukas Menkhoff; Ulrich Schmidt (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
This study tests the prediction that perceived corruption reduces ethical behavior. Integrating a standard "cheating" experiment into a broad household survey in rural Thailand, we find clear support for this prediction: respondents who perceive corruption in state affairs are more likely to cheat and, thus, to fortify the negative consequences of corruption. Interestingly, there is a small group of non-conformers. The main relation is robust to consideration of socio-demographic, attitudinal, and situational control variables. Attendance of others at the cheating experiment, stimulating the reputational concern to be seen as honest, reduces cheating, thus indicating transparency as a remedy.
Keywords: O12; D73; D91; 330; corruption; cheating; individual characteristics; lab-in-the-field experiment